2017
DOI: 10.1016/j.jmapro.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

3D printing for rapid sand casting—A review

Abstract: There are many 3D printing technologies available, and each technology has its strength and weakness. The 3D printing of sand moulds, by binder jetting technology for rapid casting, plays a vital role in providing a better value for the more than 5000 years old casting industry by producing quality and economic sand moulds. The parts of the mould assembly can be manufactured by precisely controlling the process parameters and the gas producible materials within the printed mould. A functional mould can be manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(100 citation statements)
references
References 31 publications
0
87
0
1
Order By: Relevance
“…Consequently, 3DP represents a step forward towards autonomous casting in which a sand mold can be printed without any machining stage. In this regard, (Upadhyay et al, 2017) published an extensive literature review elsewhere, so only the key features of additively processed sand molds are reminded in the present article.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, 3DP represents a step forward towards autonomous casting in which a sand mold can be printed without any machining stage. In this regard, (Upadhyay et al, 2017) published an extensive literature review elsewhere, so only the key features of additively processed sand molds are reminded in the present article.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available AM techniques, the powder-based ink-jet 3D printing, which is based on the basis of a chemical reaction between silica sand powder and an acidic binder, is widely used to manufacture sand molds. An extensive literature review in this area of research [8] and a few studies on the relationship between the properties of the 3D printed specimen and processing parameters [9,10] have been recently published.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the curing cycle of parts fabricated with ZCAST® was optimized by taking into account the potential casting defects due to offgassing of volatile binder components [22,23]. These works showed that using higher amounts of binder (8-9%) than the standard values in casting sand (1.4%) results in more offgassing and incomplete filling of the mold [8,22,23]. The same aspects were also studied in the case of an ExOne TM 3D printer, finding that the specimens had high mechanical strength (~1.3 MPa) with less amount of binder than in ZCAST system, due to the well-controlled distribution of silica sand and furan resin binder [23].…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows a combination of additive manufacturing, in which fused filament fabrication (PLA) is used to produce the intermediate investment model to be cast in ceramic block by investment casting. Although there are already studies that use similar techniques (e.g., 3D printing of sand molds [52][53][54][55][56], wax, and PLA/ABS [52][53][54][55][56]), the proposed study recurs to vacuum as an auxiliary technique for the filling of thin-rib and high aspect ratio complex three-dimensional metallic scaffolds. Additionally, vacuum is also used to promote the sanity of the resultant samples, as it is known to reduce oxide inclusion [57,58] and porosity [59,60].…”
Section: Introductionmentioning
confidence: 99%